Detection of raw pork targeting porcine-specific mitochondrial cytochrome B gene by molecular beacon probe and real-time polymerase chain reaction - Mohd Yusop, Mohd Hazim (2012)
A real-time polymerase chain reaction (PCR) assay with molecular beacon probe was developed for the detection of pork in raw states. The method combined the swine-specific primers and molecular beacon probe to specifically amplify a 119-bp fragment of porcine mitochondrial cytochrome b (mt-cyt b) gene. Mitochondrial genes are present in multiple copies and thus ensure available targets even in degraded samples. A pair of 18-nucleotide swine-cytb-specific primers were designed using Primer 3 Plus software. On the other hand, a 34-nt molecular beacon probe was designed using Beacon Designer 4 software. The porcine specificity of the primers and probe were checked by basic local alignment search tools (BLAST) to avoid mismatches with other species. A specificity test with 10 ng DNA of nine common meat providing land and aquatic species yielded a Cq value of 18.70±0.12 to 19.08±0.06 only with the pork DNA in a 40 cycle PCR reaction, demonstrating the swine specificity of the primers and probe. The swine-specificity was further confirmed in a binary mixture of pork and beef. The method detected 0.1% pork in binary pork-beef mixture with a Cq of 25.79±0.20. A sensitivity test with 10-fold serial dilution revealed that the assay can determine 0.0001 ng of porcine DNA with a PCR efficiency of 96% with a good reproducibility, precision and high correlation coefficient (r2=0.9989). The shorter length target (119-bp) and strong sensitivity and specificity suggest the method can be used for the routine analysis of pork adulteration in raw meats.